2020
DOI: 10.1088/1757-899x/712/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dried Sewage Sludge on Compressive Strength of Concrete

Abstract: Sewage sludge is a waste product generated from the wastewater treatment process at the treatment plant. The amount of sewage sludge produced is increases every year as the population increased. Poor management of sewage sludge will give negative impact to the environment. Replacing cement with sewage sludge ash is more significant to reduce the amount of waste material from sewage treatment plants. In this study, the various percentage of dried sewage sludge (DSS) has been added to replace the cement. Sewage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The sewage sludge ash analyzed in this paper meets the standard conditions to be used as an additive in the cement industry: the content of SO 3 of ash is less than or equal to 4%, the compressive strength at 28 days is greater than or equal to 42.5 MPa, and the initial setting time is greater than or equal to 60 min [15,17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sewage sludge ash analyzed in this paper meets the standard conditions to be used as an additive in the cement industry: the content of SO 3 of ash is less than or equal to 4%, the compressive strength at 28 days is greater than or equal to 42.5 MPa, and the initial setting time is greater than or equal to 60 min [15,17].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, between 2000 and 2018, cement production increased, with an average annual growth rate of 6.2%, reaching 4200 million tons in 2018, compared to 1600 million tons produced in 2000, as seen in Figure 1 [7]. In this paper, sewage sludge ash as raw material for the cement industry has been analyzed [8,[17][18][19]. The ash of sewage sludge comes from the incineration of sewage sludge from wastewater treatment plants, and has a high porosity, and irregular sand-like shape.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The compressive strength was reported to be dropped from 17 MPa to 7 MPa with the increasing amount of water-treatment plant sludge addition from 5% to 30% at 1000°C sintering temperature [25]. Another study showed the decrease in compressive strength of concrete when cement was replaced with dried sewage sludge [26]. Incorporating the waste polysilicon sludge in concrete up to 20% replacement level resulted in the increase in compressive strength after 28 days of curing period [27].…”
Section: Wykorzystanie Odpadów Szlamowych Z Dżinsu Tekstylnego W Zast...mentioning
confidence: 99%